1998
DOI: 10.1038/sj.ejcn.1600542
|View full text |Cite
|
Sign up to set email alerts
|

High fat versus high carbohydrate nutritional supplementation: a one year trial in stunted rural Gambian children

Abstract: Objective: The study tests the hypothesis that a low daily fat intake may induce a negative fat balance and impair catch-up growth in stunted children between 3 and 9 y of age. Design: Randomized case-control study. Setting: Three rural villages of the West Kiang District, The Gambia. Subjects: Three groups of 30 stunted but not wasted children (height for age z-score 72.0, weight for height zscore ! 7 2.0) 3±9 y of age were selected by anthropometric survey. Groups were matched for age, sex, village, degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…cereal‐based food), it is more likely that it will be used in place of regular meals, whereas a supplement like FS may be added to cereals to make an ‘improved’ food or may be given as a snack. This theory is supported by data from our research group and from a study in Gambia that compared supplementation with FS to maize‐soy porridge and high‐fat to high‐carbohydrate supplements, respectively (Krahenbuhl et al . 1998; Maleta et al .…”
Section: Discussionsupporting
confidence: 64%
“…cereal‐based food), it is more likely that it will be used in place of regular meals, whereas a supplement like FS may be added to cereals to make an ‘improved’ food or may be given as a snack. This theory is supported by data from our research group and from a study in Gambia that compared supplementation with FS to maize‐soy porridge and high‐fat to high‐carbohydrate supplements, respectively (Krahenbuhl et al . 1998; Maleta et al .…”
Section: Discussionsupporting
confidence: 64%
“…The possibility that caregivers were compensating for their child's nutritional state must be noted. Previous studies have reported that stunted children had higher energy and protein intakes per kg body weight than non-stunted children in developed countries, indicating that stunted children were fed more food (Walker et al, 1990;Krahenbuhl et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, not only is total energy expenditure in early life similar to that in a normal healthy population from the United Kingdom (Vasquez-Velasquez, 1988), suggesting that disease does not in this case &&poach'' the energy required for growth, but supplementation of the infant diet (Krahenbuhl et al, 1998) and of the lactating mother (Prentice et al, 1980) has not improved infant growth. This indicates that infant appetite, rather than food supply, could be the limiting factor.…”
Section: Introductionmentioning
confidence: 92%